Towards environmental sustainability: further evidences from decarbonization projects in Kenya’s Blue Economy - Rasowo, Joseph Ouma; Nyonje, Betty; Olendi, Robert; Orina, Paul; Odongo, Salome (Frontiers in Marine Science, 2024)
Kenya is committed to the global efforts on climate change mitigation and adaptation as seen through investments in various sustainable green and blue economy projects. In this review paper, we present the current status of what has been done, particularly on the blue carbon offset initiatives undertaken in the mangrove and seaweed ecosystems as well as the decarbonization activities at the port of Mombasa and which should form reference information for local, regional, bilateral/multilateral partners, scientists and other climate change stakeholders. The blue carbon offset projects involve mangrove conservation, reforestation and carbon credit sale as well as seaweed farming. The initiatives have several unique features amongst which are the community-led income generation systems that simultaneously act as an inducement for ecosystem preservation, co-management and benefits sharing which are recipes for economic, socio-cultural, and environmental sustainability. A notable project impact is the conferment of economic power to the locals, particularly the women and the youth The model used embraces a collaborative approach involving multisectoral engagements of both the government, multilateral organizations, NGOs, and local communities. This integrated top-down (government) and bottom-up (local community) method deliberately targets the strengthening of economic development while ensuring sustainability.